(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Review of the polemic about the role of Roman influence in the development of Iberian epigraphy on stone in north-eastern Hispania during the 2nd and 1st cent. BCE. Two models are suggested: one in the Mediterranean harbours of Emporion, Tarraco and Saguntum, three cities with a strong Roman presence or influence, where the principal concentrations of Iberian epigraphs are located along with other Latin —and Greek— inscriptions, and Roman epigraphic types arise in a monumental context; and another one in the rest of the Iberian north-eastern regions where stelae predominate as local response to the Roman inspired monumentalisation of the coastal cities. The emergence of Iberian inscriptions on stone is explained as a consequence of the process of romanization and the diffusion, in this context, of the incipient Roman epigraphic culture.